La Asamblea en mi Universidad. - Flores, Alejandro. (2020)
The training of our nation's new professionals must be aimed at develop intellectual and moral capacities in accordance with the culture, the norms and laws promulgated in our territory. The University of Otavalo is a higher education institution that bets the development of the thought of their students attached to the norms and behaviors of a society and the laws in the Ecuadorian legal regime. In this way, it has been undertaken joint work with the National Assembly of Ecuador, through the execution of a project that will be in charge of carrying out training in the regulation of the rights and responsibilities of citizens, according to what is established by our Magna Carta.